Regional, Socioeconomic, and Dietary Risk Factors for Vitamin B-12 Deficiency Differ from Those for Folate Deficiency in Cameroonian Women and Children. Issue 11 (7th October 2015) - Shahab-Ferdows, Setareh; Engle-Stone, Reina; Hampel, Daniela; Ndjebayi, Alex O; Nankap, Martin; Brown, Kenneth H; Allen, Lindsay H
Abstract: Background: Representative data on folate and vitamin B-12 dietary intake and status in low-income countries are rare, despite the widespread adoption of folic acid fortification. Objective: The purpose of this study was to evaluate folate and vitamin B-12 intake, status, and risk factors for deficiency before implementation of a national fortification program in Cameroon. Methods: A nationally representative cross-sectional cluster survey was conducted in 3 ecologic zones of Cameroon (South, North, and the 2 largest cities, Yaoundé/Douala), and information on dietary intake was collected from 10 households in each of 30 randomly selected clusters per zone. In a subset of women and their 12- to 59-mo-old children ( n = 396 pairs), plasma folate and vitamin B-12, as well as breast milk vitamin B-12, were analyzed. Results: Vitamin B-12 and folate dietary intake patterns and plasma concentrations were similar for women and children. In the subsample, 18% and 29% of women and 8% and 30% of children were vitamin B-12 (≤221 pmol/L) and folate (<10 nmol/L) deficient, respectively. Mean dietary folate ranged from 351 μg dietary folate equivalents/d in the North to 246 μg dietary folate equivalents/d in Yaoundé/Douala; plasma folate was negatively associated with socioeconomic status ( P = 0.001). Plasma vitamin B-12 deficiency was similar in the South and North, 29% and 40%, respectively, but was only 11% in Yaoundé/Douala, and was positively associated with socioeconomic status. Mean breast milk vitamin B-12 was statistically significantly lower in the North (101 pmol/L) than in the South (296 pmol/L) or Yaoundé/Douala (349 pmol/L). Conclusions: Folate intake and status are inadequate among women and young children in Yaoundé/Douala, whereas low vitamin B-12 intake and status are more common in poor and rural areas, especially in the North. Different strategies may be needed to control deficiency of these nutrients in different regions of Cameroon.